2014
DOI: 10.1038/srep07510
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived and Well-resolved Mn2+ Ion Emissions in CuInS-ZnS Quantum Dots

Abstract: CuInS2 (CIS) quantum dots (QDs) have tunable photoluminescence (PL) behaviors in the visible and near infrared spectral range with markedly lower toxicity than the cadmium-based counterparts, making them very promising applications in light emitting and solar harvesting. However, there still remain material- and fabrication- related obstacles in realizing the high-performance CIS-based QDs with well-resolved Mn2+ d-d emission, long emission lifetimes as well as high efficiencies. Here, we demonstrate the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 49 publications
3
79
0
Order By: Relevance
“…Several research groups have found that both the quaternary and d-dots were almost insensitive to temperature [61][62][63][64][65][66][67][68]. The temperature-dependent PL intensity was investigated to examine the thermal stability issue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have found that both the quaternary and d-dots were almost insensitive to temperature [61][62][63][64][65][66][67][68]. The temperature-dependent PL intensity was investigated to examine the thermal stability issue.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of transition metal ions into NCs with low intrinsic toxicity, such as Mn-and/or Cu-doped ZnSe and ZnS has been widely explored because of the unique optical properties of the doped NCs [61][62][63][64][65][66][67][68]. The doped NCs not only retain nearly all the advantages of intrinsic properties of NCs, but also possess new properties, such as enhanced thermal stability, reduced chemical sensitivity, and elimination of luminescent self-quenching and re-absorption.…”
Section: Introductionmentioning
confidence: 98%
“…8,30,31 The inset in Figure 1b gives the PL QY of the resultant QDs. 8,30,31 The inset in Figure 1b gives the PL QY of the resultant QDs.…”
Section: Synthesis and Optical Properties Of Mn 2+ -Doped Zn-in-s Qdsmentioning
confidence: 99%
“…It is reported that the intensities of the Mn 2+ -doped QDs significantly rely on the concentrations of Mn 2+ dopants. 31 If ZnS or InS nucleates separately, the corresponding absorption band edges should have various contour rather than gradually shift from ~350 to ~450 nm ( Figure 5). 22,27 However, the more In 3+ ion sites replaced by the Mn 2+ counterparts would result in the charge imbalance, which accordingly makes the PL intensity be decreased.…”
Section: Effect Of the Reaction Temperature And Amount Of Ode-s On Thmentioning
confidence: 99%
“…10,11,12,13 Nevertheless, the energy conversion efficiency of solar cells using CZTS still lags behind that for I-III-VI 2 and has not seen improvement over 12 % in recent years. 14 19,20,21,22,23 This method of alloying shifts the material's band gap beyond the useful solar absorption region and thereby diminishes their suitability in solar cells. 24 Moreover, Ga and Al analogues of these alloys have not been reported.…”
mentioning
confidence: 99%